Determinant of Smoking Behavior among Elementary Student in Indonesia: A Structure Equation Model - Novita Haryanto, Astrid; Noer, Melinda; Kusumayati, Agustin; Machmud, Rizanda; Hafizurrachman, Muhammad; Bachtiar, Adang (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND:Initial smoking exposure may occur during early adolescence (aged 10 to 12 years old), and it increases over time. Although several factors for smoking behaviors exist among adolescents, there is few studies address determinant of smoking behavior by adding others variables in theory of plan behavior such as smoking refusal skills, self-regulation, parenting, family function, environment, and culture. AIM:The aim of this study was therefore to evaluate the determinant of smoking behavior among elementary student in Indonesia using a structural equation model. METHOD:A cross-sectional survey was carried out from June to October 2019 in West Java, Indonesia. For each school, students were selected using a systematic random sampling. technique. The study included girls and boys ages 10-12. The consent was obtained by the parent or guardian. Structural equation modelling was used for analysis. RESULTS:The mean age was 10.56 years (SD= 0.37). About 28.6% of them were currently smoking with aged of first use was 10.02 (SD=0.19). more than half (56%) of their family were currently smoking too and friend smoking was 41.7%. The final model accounted for 27% and 39% of the variance of intention and smoking behaviour, respectivelyhas both direct and indirect effect through empowerment on self-care behaviors toward pregnancy-related complication. CONCLUSION:The present study was intended to expand the theory of planned behavior by including additional variables in its model: smoking refusal skills, self-regulation, parenting, family function, environment, and culture. This study also provides a significant contribute for clinical a practice and policy maker as a basic data to establish future intervention to promote no tobacco use among elementary student to achieve optimal well-being to prevent a fatal disease.